Zagier–Hoffman’s Conjectures in Positive Characteristic - Bo-Hae Im; Hojin Kim; Khac Nhuan Le; Tuan Ngo Dac; Lan Huong Pham (Forum of Mathematics, Pi)
Multiples zeta values and alternating multiple zeta values in positive characteristic were introduced by Thakur and Harada as analogues of classical multiple zeta values of Euler and Euler sums. In this paper, we determine all linear relations between alternating multiple zeta values and settle the main goals of these theories. As a consequence, we completely establish Zagier–Hoffman’s conjectures in positive characteristic formulated by Todd and Thakur which predict the dimension and an explicit basis of the span of multiple zeta values of Thakur of fixed weight.